2016
DOI: 10.1016/j.jsxm.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Venous Thromboembolism in Transgender Women Receiving Oral Estradiol

Abstract: Introduction One of the most serious known adverse effects of feminizing cross-sex hormone therapy (CSHT) is venous thromboembolism (VTE); however, no study has assessed the incidence of VTE from the hormone therapies used in the United States because previous publications on this topic have originated in Europe. CSHT in the United States typically includes estradiol with the antiandrogen spironolactone, whereas in Europe estradiol is prescribed with the progestin cyproterone acetate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 20 publications
2
32
0
1
Order By: Relevance
“…This is consistent with the limited evidence available in the literature that transgender adults are diagnosed with more chronic conditions. 1,10,35 Potentially disabling conditions were also much more common in TMBs than CMBs, including a range of mental health, neurological, and chronic pain conditions. Our findings on the potentially disabling mental health conditions were especially notable, indicating that those conditions were much more common in TMBs than in CMBs by upwards of 20 percentage points for most conditions.…”
Section: Trans Medicare Beneficiaries and Chronic Conditions 407 Discusmentioning
confidence: 99%
“…This is consistent with the limited evidence available in the literature that transgender adults are diagnosed with more chronic conditions. 1,10,35 Potentially disabling conditions were also much more common in TMBs than CMBs, including a range of mental health, neurological, and chronic pain conditions. Our findings on the potentially disabling mental health conditions were especially notable, indicating that those conditions were much more common in TMBs than in CMBs by upwards of 20 percentage points for most conditions.…”
Section: Trans Medicare Beneficiaries and Chronic Conditions 407 Discusmentioning
confidence: 99%
“…Another retrospective study of 165 patients with matched controls demonstrated an eightfold increase in risk of VTE in transwomen treated with conjugated equine estrogen compared to oral or transdermal estradiol . One retrospective chart review of transwomen using oral estradiol found the incidence of VTE to be 7.8 per 10 000 patient‐years; patients were followed for a mean of 1.9 years with only one patient diagnosed with VTE . Although this incidence was low, with 1286 total patient‐years of follow‐up, the short duration of per‐patient follow‐up and the fact that data were based on chart review might not indicate the true thrombotic burden, as data described later suggest that the VTE risk associated with hormone therapy in transwomen continues to increase over time.…”
Section: Case I: Mtfmentioning
confidence: 99%
“…47 Because of this, intraoperative VTE prophylaxis in the form of subcutaneous heparin and sequential compression devices are essential. 49 …”
Section: Intraoperative Carementioning
confidence: 99%